Preparation and characterization of oxidized starch-chitosan complexes for adsorption of procyanidins. (January 2020) - Ji, Ying; Lin, Xun; Yu, Jicheng
Abstract: This study developed oxidized starch-chitosan complexes for the adsorption of procyanidins. Oxidized starch-chitosan complexes were prepared in two steps. Native cornstarch was first oxidized with a 2, 2, 6, 6-tetramethyl piperidinyloxy (TEMPO) mediated reaction and then surface coated with chitosan to adsorb procyanidins. This study evaluated the morphologies and structures of starches in addition to the adsorption properties of procyanidins onto oxidized starch-chitosan complexes. The zeta potential revealed that the optimal weight ratio of oxidized starch and chitosan in the complexes was 1:0.4. The UV–visible spectrum of the complexes showed absorption spectra at about 255 nm, which has never been observed for oxidized starch. X-ray analysis and SEM indicated that the complexes changed the crystallinity and morphology of native starch. The ATR-FTIR spectra suggested that electrostatic interactions may be present between the -COO - of oxidized starch and –NH3 + of chitosan. The adsorb experiments suggested that the oxidized starch-chitosan complexes could potentially be applied as carriers of bioactive compounds. This paper provides a good reference for an efficient adsorbent of polyphenols by oxidized starch-chitosan complexes. Highlights: Corn starch was modified by TEMPO mediated reaction and chitosan adsorption. The adsorption capacity of procyanidins was increased by oxidized starch-chitosan complexes. Chitosan plays a decisive role to increase the adsorption capacity of modified starch.